Anomalous absorption of hydrogen peroxide (H2O2) rotational transitions. (August 2020) - Sharma, Mohit K.; Chandra, Suresh
Highlights: Sobolev analysis of H2 O2 is performed. Besides four astronomically detected lines, 24 lines are found to show emission features. 16 lines of H2 O2 are found in anomalous absorption. Additional 24 lines are found to show emission feature. Additional 40 lines along with detected ones may help in the detection of H2 O2 . Abstract: Hydrogen peroxide (H2 O2 ) is considered to play important role in the chemistry of ozone layer in the troposphere. It also has been detected first time in the cold environment of a star-forming region towards ρ Oph A. According to the selection rules for dipole allowed transitions, the H2 O2 ro-torsional levels may be classified into four distinct groups. Using the spectroscopic information (rotational and centrifugal distortion constants, and electric dipole moment), we have calculated energies of lower 50 levels of each group, and radiative transition probabilities for transitions between the levels. Using these radiative transition probabilities along with the collisional rate coefficients (obtained with the help of a scaling law), we have solved, for each group, a set of 50 statistical equilibrium equations coupled with the equations of radiative transfer and have found 16 lines showing anomalous absorption. In addition to four astronomically detected lines, 24 lines are found to show emission features. All these lines may play a significant role for the identification of H2 O2 in the interstellar medium.